Biodiversidade aquática e impactos ambientais : percepção e proposta de ensino por atividades investigativas - (:unkn) unknown (Universidade Estadual de Goiás, 2016)
Non-formal teaching spaces have a high educational potential, enabling the implementation of a knowledge less elaborate levels to more elaborate and complex levels. In these environments, the use of investigative activities as a starting point to develop an understanding of concepts is a way to get students to participate in their learning process. We believe it is essential for scientific education work related to environmental issues in order to obtain a population informed and aware of its responsibility in environmental protection. The objective of this study was to analyze the perception of elementary school students from public schools on aquatic biodiversity and the influence of environmental impacts on this biodiversity, and to propose and analyze an investigative activity in science education for teaching environmental issues, with development of a didactic sequence may grant teachers to serve minister classes related to the topic in other learning environments. It is a qualitative and quantitative research that has developed in three stages. At first data were collected through questionnaires and drawings with students from 7th year of basic education in public schools in Goiás, with the aim of analyzing the perception of these students about aquatic biodiversity and environmental impacts on aquatic environments. It was later developed a teaching sequence for teaching these subjects in a non-formal learning environment using as methodology investigative activities. And then was elencada one 7th grade class with 23 students who carried out these investigative activities on aquatic environmental impacts in the Laboratório de PesquisasEcológicas e EducaçãoCientífica da UniversidadeEstadual de Goiás (LABPEEC / UEG) and Trilha do Tatu. We conclude that the activities proposed in this investigative work contributed to the expansion of knowledge of children about aquatic biodiversity and environmental impacts and therefore the teaching sequence can be used by other teachers as a teaching strategy on environmental impacts.
Aquatic biodiversity and environmental impacts : perception and teaching proposal by investigative activities
Keywords: Ensino de Ciências; Ambientes não formais de ensino; Conservação ambiental; Science Teaching; Non-formal learning environments; Environmental Conservation; EDUCACAO::ENSINO-APRENDIZAGEM